Penerapan Metode Preference Rangking Organization Methof for Encrichment Evaluation (PROMETHEE II) Dalam Penyeleksian Penyiar Radio - Emi Safitri; Abdul Sani Sembiring; Suginam Suginam (STMIK Budi Darma, 2021)
One of the media that presents information quickly and is supported by high technology, one of which is radio. Radio as the oldest and most familiar communication media tool in the world continues to survive amidst many new media such as the internet. Radio up to now is still believed to be an information and communication media tool favored by many people because it has an important role in disseminating information about information about education, entertainment or other advertisements and events. To convey this information needed Human Resources (HR) is needed, namely broadcasters. In selecting the radio broadcaster must meet the requirements or criteria, so that they are chosen to be broadcasters. One solution to these problems is right by using a Decision Support System (SPK). Decision Support System (SPK) can help radio stations in making decisions on the selection of good radio broadcasters and increasing the efficiency of the decision. The promethee II method is one of the Multi Criteria Decision Making (MCDM) methods which means that it determines or sequences in a multicriteria analysis, this method is known because the concept is efficient and simple, in addition to solving problems related to multicriteria, others.